Extra-oral approach to iatrogenic temporomandibular joint dislocation-case report - Munjal, Manish; Munjal, Shubham; Sharma, Salony; Kaur, Hardeep; Chawla, Deeksha; Sandhu, Loveleen; Gupta, Dhruv; Sawhney, Mehneet; Pillai, Anjana (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
We discuss an intriguing patient whose temporo-mandibular joint got dislocated following, a per oral sialodochotomy. The reduction was undertaken using an external approach rather than the conventional internal without sedation. The approach is quick, painless, easy to perform, reproducible and least expensive. This technique is based on the following principles i.e., in the anteriorly dislocated mandible, the coronoid process and anterior border of the ramus can be palpated easily over the cheek on the affected side and thus steady pressure application on the cheek over the coronoid process and anterior aspect of the mandibular ramus, easily reduce the dislocation. In the undislocated mandible, the coronoid process and anterior border of the ramus are not palpable as they are located posterior to the body of the zygoma